2008
DOI: 10.1016/j.limno.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial population and chemistry in the bottom sediment of a laterally subdivided drinking water reservoir system

Abstract: Sediments in standing waters are complex habitats that are able to provide favorable living conditions for manifold microbial species. The aim of this study was to investigate the spatial and seasonal composition of bacteria in freshwater sediments and the chemical conditions. Four sampling points were investigated at monthly intervals along the flow of water from a pre-reservoir down to the main dam of the Saidenbach reservoir, a drinking water reservoir located in Saxony, Germany. Selected chemical criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
15
1
3
Order By: Relevance
“…It is suggested that the microbial populations in the hypolimnion could be enhanced by various factors, such as extracellular enzymes of anaerobic metabolism [47,48], the biomass and organic matters exported from the upper waters, the complex interaction with the massive microorganisms in the sediment [10], and the release of nutrients from the sediment [9,49]. Although we did not measure changes in organic matter directly in the water bodies, we cannot exclude the possibility that the contaminants in the deeper layer can be metabolized in various ways due to the differences detected in the utilization of 31 different kinds of carbon sources by using the Biolog method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the microbial populations in the hypolimnion could be enhanced by various factors, such as extracellular enzymes of anaerobic metabolism [47,48], the biomass and organic matters exported from the upper waters, the complex interaction with the massive microorganisms in the sediment [10], and the release of nutrients from the sediment [9,49]. Although we did not measure changes in organic matter directly in the water bodies, we cannot exclude the possibility that the contaminants in the deeper layer can be metabolized in various ways due to the differences detected in the utilization of 31 different kinds of carbon sources by using the Biolog method.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been performed to determine the microbial composition of aquatic habitats, using molecular methods such as denaturing gradient gel electrophoresis (DGGE) [9], catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH) [10], clone library analysis [11], and 454-pyrosequencing [12,13]. The Biolog EcoPlate™ has also been developed to study heterotrophic microbial communities based on carbon-source utilization as a more simple and rapid method, and has been widely used in various environments, including soil, sediments and activated sludge [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Röske et al [4,5] used CARD-FISH and 454 GS FLX pyrosequencing to investigate sediment bacterial and archaeal communities from a mesotrophic drinking water reservoir located in Saxony, Germany. Recently, Huerta et al [14] also determined the sediment bacterial communities in three water supply reservoirs located near Barcelona, Spain using Roche 454 GS FLX pyrosequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Acid-volatile sulfide (AVS) was extracted by exposure the wet samples to concentrated hydrochloric acid by using steam distillation and was trapped in a solution of sodium hydroxide and ethylenediaminetetraacetic acid (EDTA). The trapped sulfides were measured using a DR 5000 spectrophotometer (Hach Co.) (Röske et al, 2008;Kondo et al, 2012). The sulfate concentrations of the samples were measured by ion chromatography (Metrohm AG, Herisau, Switzerland).…”
Section: Analysis Of Sediment Chemical Characteristicsmentioning
confidence: 99%